PENINGKATAN PEMBELAJARAN ROLL DEPAN SENAM LANTAI DENGAN METODE VARIASI BERMAIN - Istiqomah, Umi Yaumil; Haetami, Mimi; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractImproving the results of the front roll learning with variations of play with research problems including the fifth grade students still weak in front roll floor gymnastics learning with improvement through play variation. This study uses a CAR approach (Classroom Action Research), a research conducted by bermasud to find information about the implementation of a variety of learning delivered with classroom action research. With 31 research subjects, cycle to cycle was obtained, from the table above through cycle 1 that was carried out during the roll front gymnastics learning exercise, there were 16 students who had graduated with a percentage of 52% and had not passed as many participants 15 students with a percentage of 48% followed by the next cycle 2 that have been done when learning roll front gymnastics floor there are students who have graduated as many as 29 students with a percentage of 94% and have not graduated as much as 2 students with a percentage of 4% which is still below the value kkm is 70. From the table above shows an increase between cycles from cycle 1 to cycle 2 from completeness 54% to 94% thus an increase of 40% from kkm 70.Â Keywords: Increased Front Roll, Play VariationsÂ